THE REFORM OF FRENCH CONTRACT LAW: A CRITICAL OVERVIEW - Downe, Alexis (2016)
Since the Napoleonic Code of 1804 we have seen republics, monarchies and empires coming and going; local and world wars; revolutions, from the industrial to the informational; and our society has moved from an economy based on agriculture to one open to the world, based on tertiary services. In all this time, French contract law has been able to stay up and keep up to date with the many changes in society, thanks to the judicial interpretation of the various articles of the French civil code and the generality of its articles. There have been many previous attempts to reform French contract law but its principles, forged in 1804, have escaped unscathed, except for certain transpositions of European directives. This article focuses on an academic point of view with regards the reforms to the French civil code that will bring private contract law into line with modern international standards. This is the first step in a series of broader changes the government is making to the French law of obligations. This reform is said to have both adapted and revolutionised French contract law and merits scholarly attention.